2018
DOI: 10.1002/jor.23886
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal loading of the hip and knee joints in unilateral hip osteoarthritis persists two years after total hip replacement

Abstract: A total hip replacement (THR) is a common and routine procedure to reduce pain and restore normal activity. Gait analysis can provide insights into functional characteristics and dynamic joint loading situation not identifiable by clinical examination or static radiographic measures. The present prospective longitudinal study tested whether 2 years after surgery a THR would restore dynamic loading of the knee and hip joints in the frontal plane to normal. Instrumented gait analysis was performed shortly before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 60 publications
(106 reference statements)
1
43
0
Order By: Relevance
“…Then the disease severity of ipsilateral hip gradually developed a degree where met the indication for THA. We agreed with the idea that the sequence of arthroplasties should depend on the severity of symptoms and the most symptomatic joint of hip or knee should be replaced rst [5,31].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Then the disease severity of ipsilateral hip gradually developed a degree where met the indication for THA. We agreed with the idea that the sequence of arthroplasties should depend on the severity of symptoms and the most symptomatic joint of hip or knee should be replaced rst [5,31].…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies demonstrated that the changes in axial alignment and abnormal loading distribution after THA may result in ipsilateral knee pain and a greater disease progression of knee [3][4][5]. However, the effect of a prior THA on the outcome of a subsequent ipsilateral TKA was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients, who already had a unilateral total hip replacement (THR) for end-stage hip OA, have an increased risk of developing OA in other joints of their lower extremities (Shakoor et al, 2002). Stief et al (2018) showed that after THR, patients reduce the external knee adduction moment (KAM) in the second half of stance of both legs compared to healthy controls whereas Shakoor et al (2003) found a significantly higher KAM in the contralateral knee. The reduction in KAM is thought to shift the load from the medial to the lateral knee compartment (Schmidt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%